Overcoming Stigma and Discrimination: Challenges for Reinsertion of Gang Members in Developing Countries - Rosen, Jonathan D. (International journal of offender therapy and comparative criminology, 2018)
This article is an effort to better understand the discrimination mechanisms that ex-gang members perceive upon leaving the gang and seeking to reinsert themselves into a society marked by high levels of violence and inequality, as in Central America. Based on 24 in-depth interviews with former members of MS-13, the 18th Street gang, and other street gangs in El Salvador, this article analyzes the different mechanisms of discrimination perceived by respondents as a result of the stigma of past gang membership. This article also documents how these perceptions of discrimination can affect individuals who are searching for employment opportunities and seeking to reinsert themselves into society.